Prevalence and psychosocial correlates of suicidal ideation among pregnant women living with HIV in Mpumalanga Province, South Africa. Issue 5 (4th May 2017) - Rodriguez, Violeta J.; Cook, Ryan R.; Peltzer, Karl; Jones, Deborah L.
ABSTRACT: Pregnant women living with HIV (WLHIV) in South Africa (SA) report higher rates of suicidal ideation than those who are HIV uninfected, and antenatal suicidal ideation has been previously associated with adverse maternal and neonatal outcomes. Few studies have attempted to identify correlates and psychosocial predictors of suicidal ideation in this population. In this study, we sought to estimate the prevalence of and identify risk factors for suicidal ideation among pregnant WLHIV in rural SA ( N  = 673). Thirty-nine percent of women endorsed suicidal ideation (95% CI: 35.2% to 42.3%) and in multivariable logistic regression analysis, suicidal ideation was associated with intimate partner violence and stigma, which interacted to multiplicatively increase the odds of suicidal thoughts. Given the high rates of reported suicidal ideation identified in this sample, and the potential harm to mothers and neonates, suicide risk assessment and management protocols for pregnant WLHIV should be considered for inclusion in the standard of care in rural SA.